A Statistical Analysis of Powder Flowability in Metal Additive Manufacturing. Issue 10 (14th June 2020) - Kiani, Parnian; Scipioni Bertoli, Umberto; Dupuy, Alexander D.; Ma, Kaka; Schoenung, Julie M.
Abstract : The quality of parts fabricated with additive manufacturing is influenced by the flowability of the feedstock particles, which is the result of many factors, including chemistry (e.g., true density, the presence of surface oxides, and impurities), morphology (e.g., particle shape and the presence of satellites), and particle size distribution. This work investigates the relationship between powder characteristics and flow behavior of different powders using three flowability testing methods. Six powders of two compositions (316L stainless steel and AlSi10Mg), made using two different methods (gas‐ and water‐atomization), are investigated to rationalize the effect of powder chemistry and morphology on flow behavior. The results show that the true density of the powders can influence several flowability metrics. In addition, aspect ratio strongly influences the initiation of flow from a static condition, whereas average particle size strongly dictates the ease of maintaining that flow. Abstract : Metal additive manufacturing is strongly influenced by powder flowability. The flow behavior of six powders of two compositions (stainless steel and AlSi10Mg) using three flowability instruments is measured. Results indicate that particle morphology strongly influences the flow initiation, which is important in powder‐bed processes. Particle size strongly influences how well flow is maintained, which is important in powder‐fed processes.